Kualitas Pelayanan Transportasi di PT Kereta Api Indonesia (Persero) Kabupaten Sidoarjo - Ismianingtyas, Rizka; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2017)
Purpose of this research is analyze and describe ticketing service effectiveness at Sidoarjo Railway Station, describe factors that impact service effectiveness. Type of this research is descriptive qualitative with informant act of determining technique snowball sampling. Primary data will be obtained from in-depth interview with key informant i.e chief of Sidoarjo railway station, 2 ticketing officers and 5 passengers in Sidoarjo railway station as informant.Result of this research reveals that service, delivered Sidoarjo railway station is effective. In terms of the responsive and polite officers, they have good capability to serve passengers, proper service deliverance, in addition to put empathy on their passengers. Yet, the provision of self-service ticket printing machine (CTM) and waiting room facility are still lack, specifically for days off. local railway ticket which can’t be purchased by online. Factors influencing service effectivity, namely, First, awareness factor, the service officers carry out their responsibility properly. Secondly, regulation factor, Sidoarjo railway station itself runs with the regulation. Thirdly, officials revenue is above the regional minimum wages (UMR). Fourthly, officers’ competency, the ticketing service officers are competent. Fifthly, facility factor the facility waiting room self-service ticket printing machine (CTM) and for passengers are not fairly yet.